Kendala Guru Sekolah Dasar dalam Memberikan Penilaian Sikap Siswa pada Proses Pembelajaran Kurikulum 2013 di Sekolah Dasar Negeri Gintung 1 - Sartika, Devi; Siregar, Epriliani Rahmita; Syurgaini, Joya; Magdalena, Ina (Lembaga Yasin AlSys, 2023)
The study is conducted aimed at getting information on the teacher's attitude assessment of the 2013 curriculum learning process at SDN GINTUNG 1. the approach used in this study is a qualitative approach with a descriptive type of research. This qualitative approach is used to describe, explain, and dig up anything related to the study. Data collection techniques in this study using observation and interviews. Data is analyzed using inductive logic, that is, from specific to general. The conclusion of this study shows that teachers give assessments of students' attitudes in the 2013 learning process at SDN GINTUNG 1 where the teacher's challenges to assessing students' attitudes in the 2013 learning process at SDN GINTUNG 1 are time constraints, the large number of students in one class and the difficulty of directing students to instill good attitudes according to the purpose of learning. The efforts of teachers in overcoming the assessing difficulties of students' attitudes in the 2013 learning process in the way of observing or observing students' attitudes during the learning process, discussions with student parents, coordination with other teachers, and asking with other students and also creating purposeful media.